Health-Related Quality of Life Based on EQ-5D Utility Score in Patients With Tuberculosis: A Systematic Review - Park, Hae-Young; Cheon, Hyo-Bin; Choi, Sun Ha; Kwon, Jin-Won (Frontiers in Pharmacology, 2021)
Background: Tuberculosis (TB) has significant effects on patients’ health-related quality of life (HRQOL) and this study was conducted to evaluate the HRQOL based on EQ-5D utility score according to various health statuses of TB patients. Methods: A systematic literature review was conducted to select articles on HRQOLs outcomes of TB patients since 2000. A total of 1,710 articles were searched for primary screening and seven studies that directly assessed all types of TB patients using the EQ-5D were finally selected. Results: The EQ-5D scores of TB patients were in the ranges of 0.43–0.70. After the completion of TB treatment, the utility weights increased to the ranges of 0.88–0.98 and the EQ VAS values showed similar trend as the results of the EQ-5D. The EQ-5D score for multi-drug-resistant TB was very low at 0.51 during treatment but increased to 0.88 after the treatment was completed. The utility weights of latent TB were not significantly different from those of the general population. Conclusion: This study showed that the HRQOL based on the EQ-5D utility score of TB patients has significantly decreased, and the TB treatment has a significantly positive effect on the quality of life of patients.